Constructing Identity Through Style: A Stylistic and Thematic Study of R. K. Narayan’s The English Teacher, The Guide and The Painter of Signs - ., Amit; Hashmi, Dr.Syed Ghufran (Journal of Ecohumanism, 2025)
R.K. Narayan is the famous author of English literature who wrote most famous novels namely The English Teacher, The Guide, and The Painter of Signs. The present paper is an attempt to explore authors simple yet powerful storytelling ability to shape the identities of his characters in novel like Krishna, Raju, and Raman. These characters started out as an ordinary man, their experiences with love, loss, ambition, guilt, and social change gradually transform how they see themselves. The emotional journey of each character sparks author’s writing style. Through a comparison of the three novels, the study demonstrates that identity is dynamic and constantly evolving due to relationships, personal challenges, and the shifting social landscape.